Experimental study and finite element simulation of deformation homogeneity between regions of commercially pure titanium deformed by ECAP (Research, Society and Development, 2022)
ECAP is a process of severe plastic deformation of a material, whose objective is to refine the grain size in the microstructure. The materials processed by ECAP show improvements in their mechanical properties. The process variables that affect the microstructure refinement are: processing route, die types, and number of passes. In the ECAP matrix used in the deformation process, the channel angle and the curvature angle determined the efficiency of the microstructural refinement. This work aims to analyze the deformation homogeneity through the mechanical processing of Ti CP via ECAP in an experimental way and by finite elements, associate the models for comparison between the levels of deformation in the external and internal regions with longitudinal section of the specimen. The Ti CP samples were deformed via ECAP in up to 8 passes, using route A, in a matrix with an intersection angle between the channels of Φ = 120º. Vickers microhardness measurements were performed at each pass to evaluate the changes caused for later association with the numerical simulation. The material was numerically simulated through the Abaqus modeling interface – 2020 version with educational license. The physical parameters were pre-established by recording the physical and mechanical variables in the software. The results were satisfactory in proving the association between the experimental and finite element studies, also indicating that there is a difference between the strain levels for the regions analyzed in both models.